Relasi Suami-Isteri Pada Keluarga Buruh Iwak Di Desa Kenanti Kecamatan Tambakboyo Kabupaten Tuban - Rini, Rini; Jatiningsih, Oksiana (Peneliti.net, 2023)
The purpose of this study is to describe and find out more about the power relations of husband and wife in decision making in fisherman families. Data collection techniques in this study used in-depth interviews and observation. The data analysis technique uses Michael Foucault's discourse analysis with an archaeological and genealogical approach. The results of this study are that there is knowledge that women must be thrifty, the husband is the head of the family who must be obeyed by the wife, and the importance of children in the family to continue the expectations of parents which are considered the truth and influence the way of thinking and acting behavior in decision making in the family fish worker. Husband-wife relations in decision-making in fisherman families still tend to be dominated by patriarchal discourse. Husband-wife power relations that express the domination of one party over another party in which the fish labor family is influenced by constructed knowledge, husband-wife relations with low economic levels are more egalitarian than husband-wife relations in families with middle economic levels.